2017
DOI: 10.1128/mbio.00939-17
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Hijacks a Noncanonical Oxidoreductase Function of a Cellular Oligosaccharyltransferase Complex

Abstract: Dengue virus (DENV) is the most common arboviral infection globally, infecting an estimated 390 million people each year. We employed a genome-wide clustered regularly interspaced short palindromic repeat (CRISPR) screen to identify host dependency factors required for DENV propagation and identified the oligosaccharyltransferase (OST) complex as an essential host factor for DENV infection. Mammalian cells express two OSTs containing either STT3A or STT3B. We found that the canonical catalytic function of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 38 publications
5
60
0
Order By: Relevance
“…Several high-throughput approaches have been applied to screen all 20,000 human genes for interactions with flaviviruses, including knockdown screens based on RNA interference (Sessions et al 2009;Kwon et al 2014;Le Sommer et al 2012) , knockout screens via haploid cell lines or CRISPR libraries (Marceau et al 2016;Lin et al 2017) , and bulk transcriptomics via microarrays or RNA-Seq (Sessions et al 2013;Moreno-Altamirano et al 2004;Fink et al 2007;Conceição et al 2010;Becerra et al 2009;Liew and Chow 2006) . While these approaches have provided important insights, our understanding of infection-triggered cellular responses is far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…Several high-throughput approaches have been applied to screen all 20,000 human genes for interactions with flaviviruses, including knockdown screens based on RNA interference (Sessions et al 2009;Kwon et al 2014;Le Sommer et al 2012) , knockout screens via haploid cell lines or CRISPR libraries (Marceau et al 2016;Lin et al 2017) , and bulk transcriptomics via microarrays or RNA-Seq (Sessions et al 2013;Moreno-Altamirano et al 2004;Fink et al 2007;Conceição et al 2010;Becerra et al 2009;Liew and Chow 2006) . While these approaches have provided important insights, our understanding of infection-triggered cellular responses is far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…OST catalytic subunits, therefore, support HSV-1 replication (and are the targets of NGI-1) by providing an important catalytic function, not a noncatalytic structural role. This contrasted with the finding that noncatalytic structural features of OST catalytic subunits were critical for dengue virus replication (26,27). Glycosylation indices for gC ( Figs.…”
Section: Discussionmentioning
confidence: 70%
“…Work with flaviviruses showed that although both STT3A-OST and STT3B-OST were necessary for dengue virus infection, these enzyme complexes acted as structural scaffolds for replicating viral components rather than as catalytic OSTs per se (26,27,29). This counterintuitive result was echoed by showing that NGI-1 impaired dengue virus replication by interaction with OST independent of its enzymatic activity (29).…”
Section: Manipulation Of Ost Accessory Subunits Supports a Primary Romentioning
confidence: 99%
See 2 more Smart Citations